Nomenclatural notes and typification of three Aquilegia (Ranunculaceae) names described from the Himalayas - Erst, Andrey S.; Boltenkov, Eugeny V.; Pendry, Colin; Wang, Wei (Phytotaxa, 2021)
As part of the ongoing revision of the Himalayas species of Aquilegia (Ranunculaceae), three names applicable to three accepted species are typified, and some nomenclatural and taxonomic remarks are provided. Lectotypes are designated for A. glauca (a taxonomic synonym of A. fragrans) and A. vulgaris subsp. nivalis (a nomenclatural synonym of A. nivalis). Epitypes for A. fragrans and A. glauca were also designated in order to avoid any ambiguity in the taxonomic interpretation of the lectotypes and hence the application of the names.